1995
DOI: 10.1007/bf01721235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ticks infected withFrancisella tularensis in natural foci of tularemia in western Slovakia

Abstract: The prevalence of ticks infected with F. tularensis was followed during a systematic surveillance in endemic area of tularemia in western Slovakia over the years 1984-93. Ticks were collected from vegetation in localities of Podunajské Biskupice, in the vicinity of the capital of Slovakia, Bratislava, near the river Danube. In total 6033 ticks, mostly adults of Dermacentor reticulatus and Ixodes ricinus (4994 and 1004, respectively) and 35 nymphs of Haemaphysalis concinna, were examined for the presence of F. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…tularensis persisted in tick populations at prevalence rates of 2-4% for 4 years in Martha's Vineyard [94]. Similarly, in Europe, Gurycová et al [53] found that F. tularensis subsp. holarctica persisted at prevalence rates of 0·2-1% in ticks in western Slovakia for 6 years in an area in which tularemia was endemic.…”
Section: Eco-epidemiology Of Tularemiamentioning
confidence: 95%
See 1 more Smart Citation
“…tularensis persisted in tick populations at prevalence rates of 2-4% for 4 years in Martha's Vineyard [94]. Similarly, in Europe, Gurycová et al [53] found that F. tularensis subsp. holarctica persisted at prevalence rates of 0·2-1% in ticks in western Slovakia for 6 years in an area in which tularemia was endemic.…”
Section: Eco-epidemiology Of Tularemiamentioning
confidence: 95%
“…The range of arthropod vectors connected with tularemia has expanded to include ticks [19,40,[53][54][55][56][57][58][59][60], mosquitoes [56,61], horse flies [56], fleas [62] and gamasid mites [3]. In Europe, much of the research on the role of arthropod vectors in the transmission of F. tularensis subsp.…”
Section: Tularemia In Vectorsmentioning
confidence: 99%
“…holarctica strain isolated from a European brown hare (Lepus europaeus) in 2007 (Permit number for animal challenge: 22.1/2703/003/2009). One animal was infected intramuscularly on its hind leg (case 1) with 10 3 colonyforming units (CFU), as ticks harbor high infectious doses of F. tularensis (Gurycová et al, 1995), and one orally with 10 5 CFU (case 2), a dose used in earlier studies in similar Class 1 species, in voles (Microtus pennsylvanicus and Microtus rossiaemeridionalis) (Olsufiev and Dunayeva, 1970;Bell and Stewart, 1983;Olsufiev et al, 1984;Sjö stedt, 2007). Hamsters were checked three times a day to record clinical symptoms.…”
Section: Susceptibility Of the Common Hamster (Cricetus Cricetus) Tomentioning
confidence: 99%
“…The tick species was not determined. In central Europe, ticks of the species Ixodes ricinus and Dermacentor reticularis have been shown to be naturally infected with F. tularensis, at a prevalence of 0.1 to 0.2% (6,8,22).…”
mentioning
confidence: 99%